Reabilitação urbana como gentrificadora e segregadora social: o caso dos parques Vaca Brava e Flamboyant - Arantes, Germana de Faria (2012)
Many strategic urban areas are degraded or abandoned, without a use or subuse, and they begin to contribute to a new image of the city when rehabilitated. However, with capitalist consideration and the insertion of neo-liberalism principles, it became normal in the practice of urban interventions to transform daily reality into scenes of a spectacle; making cities into goods to be consumed by a selected portion of society. Such interventions are now embedded in political discourses and practices of entrepreneurs, which aim economic success through the improved urban environment. To this end speculation is involved in all phases of the process, prompting and reinforcing the effects produced by these interventions. Gentrification and social exclusion are some of the consequences that occur when the government is an ally or became negligent in the face of actions against the private sector. In the city of Goiania two cases of rehabilitation in idle areas and the referred bilateral joint interests have occurred. Therefore the present study is based on two interventions - Vaca Brava and the Flamboyant parks - both in Goiania.